Seroprevalencia y estudio de factores asociados a la neosporosis canina en animales ingresados al Hospital Escuela, FCV-UBA, Argentina - Daprato, B. (2013)
Intracellular protozoan Neospora caninum, produces nervous, gastrointestinal and respiratory symptoms and muscular disorders in dogs. In order to estimate the seroprevalence of anti N. caninum antibodies, sera of 238 dogs admitted in the School Hospital at the Veterinary Science Faculty of Buenos Aires University, were analyzed in the 2011-2012 period. For this, the indirect immunofluorescence technique (IIF ) ( ? 1:50) was used, resulting in 27.3 % (95 % CI = 21.9% - 33.7%) positive for N. caninum . The highest prevalence was observed in dogs of group 2 to 10 years. An epidemiological survey was also carried out to analyze potential risk factors. No significant differences between sex, race or habit of staying or not exclusively indoor were found. Statistical association was found between positives and the habit of hunting (p < 0.05). IIF titers of 1/100 and 1/200 were the most frequent . The association between seropositive animals and hunting habits may\nsuggest the importance of the role of horizontal transmission. This paper seroprevalence of canine neosporosis is the first carried out in the School Hospital FCV -UBA .